The acute effect of Taurine ingestion on 3km running performance and force in trained middle distance runners - Balshaw, T. G.; Bampouras, T. M.; Barry, T.; Sparks, S. A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Taurine (TA) can increase force production of isolated mammalian skeletal muscle tissue while depletion of it decreases muscular function (Bakker and Berg, 2002; Hamilton et al., 2006). Although prolonged TA administration appears to benefit endurance performance in trained endurance athletes (Lee et al, 2003), little research exists examining the acute effects of TA on performance (Rutherford et al, 2006).The current study investigated the acute effect of 1000mg of TA on maximal 3km time trial (3KTT) performance and lower limb muscular force production (MFP) in well-trained, competitive middle distance runners (MDR). Methods: Six male MDR (age: mean 20.10, s = 1.11 years; 800m personal best times: mean 123.03, s = 5.18 seconds) participated in a double blind, randomised, crossover designed study. Following a standardized warm-up, participants completed a laboratory-based self-paced, maximal 3KTT on a treadmill ingesting either TA or placebo (PL), two hours prior to testing. Capillary blood lactate (LAC), glucose (GLU) and MFP during three countermovement jumps (without arm swing) were measured pre- and post-3KTT. Respiratory exchange ratio (RER), heart rate (HR), rating of perceived exertion (RPE), and split times were recorded at 500m intervals. Wilcoxon`s test was used to analyse overall 3KTT performance. All other variables were analysed using Friedman`s test, followed by Wilcoxon`s test with Bonferroni adjustment, if differences were found. Results: No significant differences (P > 0.05) were found for any of the variables between conditions. However, the TA condition demonstrated better performances in 3KTT but not MFP (TA: mean 650.00, s = 56.68 seconds; PL: mean 655.50, s = 68.22 seconds and TA: mean 1196.37, s = 133.08 N; PL: mean 1289.53, s = 243.08 N, respectively). Discussion: The failure to detect significant differences in performance between conditions indicates acute ingestion of TA may have no effect on 3KTT performance or peak lower limb MFP of well trained endurance runners in middle distance events. The findings of this study provide an insight into the acute effects of TA on both endurance and MFP performance, as previous studies indicated TA benefiting performance in longer duration exercise trials and after prolonged administration (Lee et al., 2003). The results also raise questions over the potential influence of TA on MFP in vivo (Bakker and Berg, 2002). More research is required to establish potential effects of different TA dosages on endurance performance of different duration.